Effects of vitreous angiopoietin-2 levels in rhegmatogenous retinal detachment on the macular microvascular bed (Ukrainian Journal of Ophthalmology, 2024)
Background: Our previous optical coherent tomography angiography (OCTA) study of rhegmatogenous retinal detachment (RRD) treatment has found an impaired retinal microvascular bed over a 12-month postoperative follow-up and warranted for the study of vitreous angiopoietin (Ang)-2 levels as a vascular destabilizing factor in patients treated for RRD.Purpose: To assess vitreous Ang-2 levels in patients with primary RRD and their association with OCTA-based changes in the macular microvascular bed in patients with RRD.Material and Methods: Eighty-seven patients with primary RRD were involved in the study and divided into two groups depending of the state of the macula: patients that underwent surgery for macular-on RRD (group 1) and those that underwent surgery for macular-off RRD (group 2). All patients had their vitreous samples taken and underwent subtotal posterior vitrectomy. Concentrations of Ang-2 in these samples were measured by an enzyme-linked immunosorbent assay (ELISA) kit (Human Angiopoietin-2 ELISA Kit, Thermo Fisher SCIENTIFIC, Rockford, IL, USA) in accordance with the manufacturer’s protocol. We assessed correlations of vitreous Ang-2 levels and OCTA-based parameters in patients.Results: At the preoperative vitreous Ang-2 level of 129.7 ± 51.99 pg/ml in group 1, there was a strong correlation of preoperative OCTA-based foveal avascular zone (FAZ) area, parafoveal deep capillary plexus density (PDCPD) and foveal deep capillary plexus density (FDCPD) with vitreous Ang-2 levels over the study period for group 1. At the preoperative vitreous Ang-2 level of 693.8 ± 634.7 pg/ml in group 2, there was a strong correlation of OCTA-based FAZ area, FDCPD, and PDCPD with vitreous Ang-2 levels at baseline and 12 months, and a moderate direct correlation of OCTA-based FAZ area, FDCPD, and PDCPD with vitreous Ang-2 levels at months 3 and 6.Conclusion: Vitreous Ang-2 levels were significantly lower in macula-on RRD eyes than in macula-off RRD eyes (129.7 ± 51.99 pg/ml versus 693.8 ± 634.7 pg/ml, p < 0.001). There was a strong direct correlation (p < 0.05) of Ang-2 with OCTA-based characteristics of the retinal microvascular bed (FAZ area, PDCPD and FDCPD) for both groups, which indirectly indicates the effect of the vascular destabilizing factor on the postoperative best-corrected visual acuity.
Keywords: angiopoietin-2; rhegmatogenous retinal detachment; OCT angiography; macula